Pelaksanaan Pembelajaran Matematika Melalui Moda dalam Jaringan Menurut Perspektif Guru, Siswa dan Orang Tua - Mochammad Taufan; Aan Juhana Senjaya; Srihati Srihati (Departement of Mathematics Education, 2023)
The purpose of this study was to find out how the implementation of mathematics learning through an online system during social/physical distancing situations from the perspective of teachers, students, and parents. This type of research is qualitative research using a literature study and interviews. The subjects in this study were teachers, students, and parents of grade VIII students at SMP Negeri 1 Jatibarang in the 2020/2021 school year. The result of this research is that the mathematics learning process is carried out online using Google Classroom media, Whatsapp, voice chat, and Google Form. However, the implementation process is not optimal. Many perspectives on the process of learning mathematics through an online system implemented in rural areas during the Covid-19 pandemic do not agree that the learning process is carried out online. Because, there are many obstacles faced such as unstable networks, additional expenses to buy quotas, tedious learning, not all students have smartphones, materials that are difficult to understand, and not achieving Basic Competence (KD).